Léčba a prognóza pacientů s relabovaným nebo refrakterním Hodgkinovým lymfomem nevhodných k transplantaci kmenových buněk - Móciková, H; Sýkorová, A; Stěpánková, P; Marková, J; Michalka, J; Král, Z; Burešová, L; Belada, D (Klinicka onkologie, 2014)
BACKGROUND: Relapses occur in 20-30% of patients with Hodgkin lymphoma (HL). Currently, there is no widely accepted standard treatment strategy in relapsed/refractory HL patients ineligible for autologous stem cell transplantation (ASCT). This article retrospectively evaluates survival and prognosis of patients with relapsed/refractory HL who were not suitable for high-dose chemotherapy and ASCT. New drugs and their efficacy in this indication are also disscussed. PATIENTS AND METHODS: A total of 17 patients treated with at least three lines of standard chemotherapy ± radiotherapy were analysed. High-dose chemotherapy and ASCT was not indicated due to advanced age (seven patients), chemorefractory disease (seven patients), cardiotoxicity (two patients) and insufficient stem cell collection of CD34+ cells (one patient). RESULTS: Median follow-up of the whole group after establishing the diagnosis was 3.48 years. Overall response to the second-line treatment was achieved in eight patients (47.0%). Four patients (23,5%) were classified as primary refractory after the first-line treatment and three more chemorefractory patients (17,6%) were detected after the second-line treatment. Out of 17 patients four are still alive (23,5%) in remission and 13 have died (eight due to HL progressions, four due to toxicity of the treatment and one patient with unknown cause of death). The estimated 5-year overall survival from the time of initial diagnosis was 46.3% and 30.8% when counted from the diagnosis of the first relapse. The estimated 5-year overall survival of four primary chemorefractory patients was significantly worse when compared to the group of 13 relapsed patients: 0 vs. 60.6%, p < 0,001. CONCLUSION: Prognosis of relapsed/refractory HL patients ineligible for ASCT and treated with several lines of standard chemotherapy ± radiotherapy is poor. Brentuximab vedotin is indicated in primary refractory patients in the second-line settings and in other relapsed patients in the third-line treatment. This strategy would help to increase the number of remissions, hence achieving a higher survival rate.
Keywords: recidiva; Hodgkinova nemoc; protinádorové látky; Recurrence; Stem Cell Transplantation; Antineoplastic Agents; retrospektivní studie; autologní transplantace; Hodgkin Disease; Humans; Transplantation, Autologous; lidé; Retrospective Studies; Prognosis; prognóza; transplantace kmenových buněk